Extended next-generation sequencing panel for Familial Hypercholesterolemia - Medeiros, A.M. (2021)
Familial Hypercholesterolemia (FH) is a common autosomal genetic disorder (1/250-1/500 worldwide). Clinically these patients present with high levels of cholesterol since birth, family history of hypercholesterolemia and premature cardiovascular disease. Formal genetic diagnosis includes the study of 3 genes: LDLR, APOB, PCSK9. Recently, other 5 genes have been associated with the FH phenotype (LDLRAP1, APOE, LIPA, ABCG5/8) since pathogenic variants have been identified in clinical FH patients.